Speech Quality Measurement of GSM Infrastructure Built on USRP N210 and OpenBTS Project - Marcel Fajkus; Martin Mikulec; Miroslav Voznak; Martin Tomis; Peppino Fazio (Advances in Electrical and Electronic Engineering, 2014)
The paper deals with the methodology for speech quality measuring in GSM networks using Perceptual Evaluation of Speech Quality (PESQ). The paper brings results of practical measurement of own GSM network build on the Universal Software Radio Peripheral (USRP N210) hardware and OpenBTS software. This OpenBTS station was installed in open terrain, and the speech quality was measured from different distances from the transmitter. The limit parameters of OpenBTS station with USRP N210 were obtained.